The butterfly mosque - Wilson, G. Willow, 1982- (Atlantic Monthly Press, 2010)
Documents the author's conversion from all-American atheist to Islam, a journey marked by her decision to relocate to Cairo, romance with a passionate young Egyptian, and her efforts to balance the virtues of both cultures.